(3HgLI GdCQjH aj HjGf eG aj cJGH Gddg GdYRjR ef GdZQjHs - (3CHh GdMSf YdGA GdOjf Ydj Hf YKeGf Hf EHQGgje Hf GdJQceGfj GdeGQOjfj,J (B750 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd Ydi YHOg GdcJGH CeG HYO , aEf Gddg JYGdi LYd GdbQBf GdcQje JPcQI ddYbdGA hJHUQI , dJchf CdHGHge ai eYGfjg eHJcQI s
(3BNQgG (B:s
(3GdhShGS GdTjWGf jhShS ai GdUOhQ hEPG GfRd GdPcQ QLY Edi GdbdH ahShS hGddg JYGdi CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3cJHJ CSeGA GdShQ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B311s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs